Analisis Struktur Pengelompokan Vokal Senandung Jolo melalui Perspektif Generative Theory of Tonal Music (GTTM): Analisis Struktur Pengelompokan Vokal Senandung Jolo melalui Perspektif Generative Theory of Tonal Music (GTTM) - Z, Megi (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2025)
Senandung Jolo is a traditional musical art form originating from Kumpeh Ilir District, Muaro Jambi Regency, Jambi Province. This art is commonly performed at cultural events, festivals, and several major celebrations, including the anniversary of Jambi Province. Typically, Senandung Jolo is presented through a singing technique accompanied by the striking of wooden slats placed on the performer’s knees while sitting with the legs extended forward. In addition, Senandung Jolo has been innovated into various instrumental formations, integrating both other traditional instruments and modern instruments. Its uniqueness is reflected in the linguistic aspect, particularly in the use of pantun enriched with idioms in the Muaro Jambi language. Senandung Jolo also contains distinct musical features, notably its vocal melodies that are rich in ornamental elements. This study aims to examine the creative processes of Senandung Jolo artists in crafting pantun, as well as to identify the configuration of its musical units through grouping-structure analysis based on the perspective of the Generative Theory of Tonal Music (GTTM). A qualitative approach and musical analysis were adopted as the methods to address these objectives. This research offers a structural description of the relationship between the creative process of oral language and the musical intuition of artists in Muaro Jambi. The findings concerning the correlation between pantun infused with Muaro Jambi idioms and the musical events within Senandung Jolo are expected to broaden readers’ insight into understanding a cultural product.